Filsafat Nilai dan Transformasi Sosial: Perspektif Sutan Takdir Alisjahbana - M. Anzaikhan; Katimin Katimin; Adenan Adenan (Al-Widad, 2025)
Alisjahbana is an Indonesian thinker who focuses on the concept of values as an important foundation for modernization, as well as the challenges faced in implementing modern values amid the dominance of traditional values. The method used is a descriptive analytical study of literary works, particularly novels, to illustrate the conflict between traditional and modern values, as well as to offer adaptation solutions. The result of this study is a deeper understanding of the challenges and gaps that arise in the implementation of Alisjahbana’s ideal values in Indonesian society. The discussion concludes that collective efforts from all parties, including public policy reform and holistic education, are needed to address the gap between ideal values and their practical implementation in society.